A SINGLE RECESSIVE MUTATED GENE (sd237-1) CONTROLING SEMI-DWARF PLANT STATURE OF RICE - Sobrizal (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
Dwarfism is a valuable trait in crop breeding, because it increases lodging resistance and decreases damages due to wind and rain. During the course of this study, a semi-dwarf mutant was successfully induced through 200 Gy gamma ray irradiated KI 237 seeds. KI 237 is a pure line with high yield potency, developed through an Indica-Japonica cross of IR36 / Koshihikari. The selected semi-dwarf plant reached 60 — 62 % of plant height of original plant KI 237 at the mature stage. The length of internodes, panicle, and seed were also compared between these two plants. The retardation of the 1st (uppermost) internodes was 24 %, moreover, the retardation of panicle and seed length were only 10 % and 2 %, respectively. The elongation pattern of the internodes in this mutant was almost the same as sd1 (Dee-geo-woo-gen), the original parent of the first release modern rice variety, but their performances were different. Based on the segregation analysis in M2 and M3 generation it was concluded that this mutant was controlled by a single recessive mutated gene. This gene was designated as sd237-1. This mutant should be useful as a genetic resource for the improvement of KI237 line through back-cross breeding as well as be developed further in breeding program directly to be a new high yielding mutant variety.